2020
DOI: 10.35609/gjbssr.2020.8.1(5)
|View full text |Cite
|
Sign up to set email alerts
|

Audit Report Lag: Specialized Auditor and Corporate Governance

Abstract: Objective - This paper aims to obtain empirical evidence about the influence of specialized auditors, audit tenure, audit committee, board independence, ownership concentration, and auditor quality on audit report lag in Indonesian manufacturing firms. Methodology/Technique – The population is all manufacturing companies listed on the Indonesia Stock Exchange between 2010 and 2016. Multiple linear regressions was used as the data analysis method. Finding - The results of this research show that specialized aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In this work, these categories have been added to resemble the homogeneous categorization at the international level, knowing that some details in the original information are lost in this process. In this way, the registration number is also more significant for each level [80]. Category 1 will now be the sum of category 0 (Less than 5 years of schooling) with category 1 (Primary Studies) [81].…”
Section: Category Samplesmentioning
confidence: 99%
“…In this work, these categories have been added to resemble the homogeneous categorization at the international level, knowing that some details in the original information are lost in this process. In this way, the registration number is also more significant for each level [80]. Category 1 will now be the sum of category 0 (Less than 5 years of schooling) with category 1 (Primary Studies) [81].…”
Section: Category Samplesmentioning
confidence: 99%
“…This resulted in the KAP which may also be an industry specialization auditor with another definition in a different reference to be annulled. (5) Due to the focus of research on mining companies, the results of this study cannot be used to generalize audit delays to other industrial companies in Indonesia during 2016-2018. (6) For the next researchers might be able to examine the research with other additional variables such as solvability, profitability or other firm performance variables that might give an updated result regarding audit delays.…”
Section: Conclusion Limitations and Suggestionsmentioning
confidence: 99%
“…Stated that auditors who are predicated as industry specialties can complete the audit process on financial statements faster than auditors who are not industry specialties, this is because specialized auditors are believed to have the ability to detect errors better, increase efficiency and knowledge about the honesty of financial statements. [3,5,6] stated that companies audited by auditors with a high level of industry specialization have a low level of audit delay. However, research by [7] found the opposite result.…”
Section: Introductionmentioning
confidence: 99%
“…‫اجعة‬ ‫الرا‬ ‫ا‬ ‫دا‬ ‫ليى‬ ‫الحباعا‬ ‫اقا‬ ‫ما‬ ‫لةةع‬ ‫خ‬ ‫ار‬ ‫إلى‬ ‫الرالةة‬ (Diana,2018;Viet et al,2018;Abdillah et al,2019;Shofiyah & Suryani,2020;Yuliusman et al,2020 (Al-Ajmi,2008;Afify,2009 ;Abernathy et al,2014;Sultana et al,2015;Ghafran & Yasmin,2018;Oussii & Taktak,2018;Viet et al,2018;Shofiyah & Suryani,2020;Yuliusman et al,2020;Firnanti & Karmudiandri, (Samaha & Khlif,2017;Diana,2018;Raweh et al,2019;Hasballah & IIyas,2019;Aljaaidi et al, Afify,2009;Samaha & Khlif,2017;Ghafran & Yasmin,2018;Viet et al,2018;Yuliusman et al,2020;Pradipta & Zalukhu, (Al-Ajmi,2008;Afify,2009 ;Abernathy et al,2014;Almuzaiqer et al,2018;Oussii & Taktak,2018;Viet,2018;Badawy & Aly,2018;Abdillah et al,2019;Raweh et al,2019;Hasballah & IIyas,2019;Shofiyah & Suryani,2020;Yuliusman et al, (Ika & Ghazali,2012;Abernathy et al,2014;Sultana et al,2015;Diana,2018;Raweh et al,2019;Hasballah & IIyas,2019…”
Section: ‫ملخص‬ ‫البحث‬mentioning
confidence: 99%